Control of articulated robot arm with sensory feedback: laser beam tracking system - Furuta, K.; Kosuge, K.; Mukai, N. (IEEE transactions on industrial electronics (1982), 1988)
A method for the trajectory tracking control of an articulated robot arm using sensory feedback is presented. First, a general control algorithm for such a problem is presented. To implement sensory feedback effectively, the dynamics of a robot arm is described in the task coordinate system. Then the dynamics of the robot arm in the task coordinate system are linearized using nonlinear feedback. Because the linearization cannot be done completely because of variations and identification errors of the physical parameters of a robot arm, a robust controller is designed so that the effect of parameter variations and errors can be lessened. The control law is shown to be simplified by the use of high-gain feedback. The simplification can make the implementation of the control law very easy. The proposed algorithm is applied to the trajectory-tracking control of an articulated robot arm using a laser beam. The experiments show that the proposed algorithm works well for such a sensory feedback system.< >